(3GddLfI GdNeGSjI eMceI GdfRGYGJ GdYeGdjI ai VhA bGfhf GdYed GdeUQi (B: s (3OQGSI ebGQfI (B/ s - (3Ydi MSf GHQGgje YeGQIs; (3GMeO MSf GdHQYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3deG cGfJ LeghQjI eUQ GdYQHjI bO GJLgJ eDNQG Gdi GdGNP HfXGe GdGbJUGO GdMQ (B: (3Gi GdjGJ GdShb (B: (3HYO GfVeGegG Gdi GJaGbjGJ GdJLGQI GdYGdejI (B: (3abO GbJVi Pdc GUOGQ bGfhf Yed LOjO (B: (3jJeTi eY GdhVY GdLOjO (B: (3hHUaI NGUI HYO HOA SjGSI GdNUNUI (B: (3Gi JMhjd GdbWGY GdYGe Gdi GdbWGY GdNGU (B: (3hbO GHQeJ GJaGbjI Hjf GdMcheI GdeUQjI hefXeI GdYed GdOhdjI (B: (3HTCf GYOGO h GUOGQ bGfhf Yed LOjOs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2006s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B197-200s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GddLfI GdNeGSjIs; (3bGfhf GdYed GdeUQis; (3eMceI GdfRGYGJ GdYeGdjIs; (3aUd GdYGeds; (3GddLGf GdEOGQjI PGJ GdENJUGU GdbVGFjs; (3eLdS GdMceGAs; (3GdeUGdMI hGdJhajbs; (3eQMdI GdJMVjQs; (3GdefGRYGJ GdaQOjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs